2012
DOI: 10.1002/pola.26355
|View full text |Cite
|
Sign up to set email alerts
|

The role of solvent‐ligated metal(II) complexes incorporating (fluoroalkoxy)aluminates as weakly coordinating anions in isobutylene polymerization

Abstract: Nitrile-ligated copper(II) and zinc(II) complexes comprising (fluoroalkoxy)aluminates as weakly coordinating anions (WCAs) have been synthesized and applied for the polymerization of isobutylene at room temperature (30 C). The polymers obtained are in the low and moderate molecular weight range and show characteristics of the highly reactive polyisobutylene. Results indicate that the fluoroalkoxy aluminate WCAs have even a higher tolerance toward water in IB polymerization than the earlier tested perfluorobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(73 reference statements)
3
18
0
Order By: Relevance
“…Recently, it was also demonstrated that the copper (II) and zinc (II) complexes associated with the perfluoroalkoxyaluminates, in particular the [Al(OC(CF 3 ) 3 ) 4 ] − counteranion as shown in Figure 3(WCA 4), can also be applied for the polymerization of IB at 30 °C 47. Similar results were obtained with the perfluoroalkoxyaluminates as with the perfluoroborate WCAs.…”
Section: Room Temperature Polymerization Of Ibsupporting
confidence: 52%
See 3 more Smart Citations
“…Recently, it was also demonstrated that the copper (II) and zinc (II) complexes associated with the perfluoroalkoxyaluminates, in particular the [Al(OC(CF 3 ) 3 ) 4 ] − counteranion as shown in Figure 3(WCA 4), can also be applied for the polymerization of IB at 30 °C 47. Similar results were obtained with the perfluoroalkoxyaluminates as with the perfluoroborate WCAs.…”
Section: Room Temperature Polymerization Of Ibsupporting
confidence: 52%
“…As already indicated, in the recent years new polymerization strategies have appeared for the preparation of PIB, which are based on initiator or metal complex systems associated with weakly coordinating anions (WCAs) 34–47…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
See 2 more Smart Citations
“…The exo‐olefin terminated PIB is also referred to as “highly reactive” PIB (HR PIB), since it readily reacts with maleic anhydride in a thermal “ene” reaction to produce PIB succinic anhydride that can be converted to polyisobutenylsuccinimide, used as ashless dispersants. In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB . Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application .…”
Section: Introductionmentioning
confidence: 99%